Earnings Discrimination in the Workplace - John Forth; Nikolaos Theodoropoulos (Global Labor Organization (GLO), 2022)
This paper provides an overview of theory and empirical evidence on earnings discrimination within the workplace. Earnings discrimination occurs when employees producing work of equal value are differentially remunerated because of their social group. The paper reviews theories of why employers may discriminate in this way. The paper then goes on to review research evidence on earnings discrimination as one source of earnings inequality within the workplace. The ability of empirical studies to identify discrimination is discussed, and evidence on the mechanisms through which discrimination may affect earnings is reviewed, covering observational and experimental studies. The research evidence is most plentiful in respect of discrimination by gender. Accordingly, much of the discussion focuses on the role of discrimination in driving a wedge between the wages of men and women. However, the paper also reviews evidence on earnings discrimination by race or ethnic group. It concludes with a discussion of policy responses.
Keywords: J71; J31; 330; earnings discrimination; gender wage gap; ethnic wage gap